Hubungan Sikap Siswa dengan Perilaku Penerapan Memakai Masker, Mencuci Tangan, Menjaga Jarak, Menjauhi Kerumunan, dan Mengurangi Mobilisasi dalam Pencegahan Penularan Covid-19 - Atira Atira; Ayu Astuti; Dianto Dianto (Health Idea, 2023)
ABSTRACT Covid-19 in West Java ranks second in Indonesia with 709,602 cases, of which 693,921 cases recovered, and 14,761 died. In Cimahi City there were 13218 positive cases, 12820 recovered cases, and 239 dead cases. One of the triggers for the Covid-19 incident was due to a lack of implementing 5M behavior (wearing masks, washing hands, keeping distance, staying away from crowds, and reducing mobilization) in prevention transmission of Covid-19. Attitude is thought to be one of the determining factors in the behavior of implementing 5M. The purpose of this study was to determine the relationship between attitude and behavior in implementing 5M in preventing the transmission of Covid-19 at MTs (Madrasah and Tsyanawiyah) Pasundan Cimahi. The research method uses cross sectional analytic surveys. The sample size in this study was 73 respondents using the Total Sampling Technique. Data collection using a questionnaire. The results of the study were analyzed univariately and bivariately with the Chi-Square test. From 73 respondents, 64.4% of the respondents got a "positive" attitude and the highest 5M implementation behavior was in the "bad" category, namely 50.7% of the respondents. Based on the bivariate analysis of data, the highest was 47 (64.4%) of respondents who were "positive" and those who behaved "badly" were 37 (50.7%) of respondents. The results of the Chi-Square analysis obtained a p value of 0.000 ≥ 0.05. The results of the study show that there is a significant relationship between the attitudes of respondents and the behavior of implementing 5M (p value of 0.000 ≥ α (0.05) then Ho is rejected or Ha is accepted. Suggestion: health facilities are needed in schools related to the behavior of implementing 5M in schools, so that students avoid the incident of Covid-19.Keywords: covid-19; attitude; behavior of implementing 5M ABSTRAK Covid-19 di Jawa Barat menempati urutan kedua di Indonesia sebanyak 709.602 kasus, diantaranya 693.921 kasus sembuh, dan 14.761 meninggal dunia. Di Kota Cimahi terdapat 13218 kasus positif, kasus sembuh 12820, dan kasus meninggal 239. Salah satu pemicu kejadian Covid-19 tersebut adalah karena kurangnya perilaku penerapan 5M (memakai masker, mencuci tangan, menjaga jarak, menjauhi kerumunan, dan mengurangi mobilisasi) dalam pencegahan penularan Covid-19. Sikap diduga merupakan salah satu faktor penentu dalam perilaku penerapan 5M. Tujuan penelitian ini adalah untuk mengetahui hubungan sikap dengan perilaku penerapan 5M dalam pencegahan penularan Covid-19 di MTs (Madrasah dan Tsyanawiyah) Pasundan Cimahi. Metode penelitian menggunakan survei analitik Cross Sectional. Besaran sampel pada penelitian ini sebanyak 73 responden dengan Teknik Total Sampling. Pengumpulan data menggunakan kuisioner. Hasil penelitian dianalisis secara univariat dan bivariat dengan uji Chi-Square. Sebanyak 73 responden, didapatkan gambaran sikap “Positif” 64,4% responden dan perilaku penerapan 5M yang tertinggi kategori “buruk” yaitu 50,7% responden. Berdasarkan analisis bivariat data yang tertinggi yaitu 47 (64,4%) responden yang bersikap “Positif” dan yang berperilaku “buruk” yaitu 37 (50,7%) responden. Hasil analisis Chi-Square didapatkan p value 0,000 ≥ 0,05. Hasil penelitian ada hubungan yang signifikan antara sikap responden dengan perilaku penerapan 5M  (nilai p sebesar 0,000 ≥ α (0,05) maka Ho ditolak atau Ha diterima. Saran: diperlukan fasilitas kesehatan di sekolah yang berhubungan dengan perilaku penerapan 5M di sekolah, agar siswa terhindar dari kejadian Covid-19.Kata Kunci: covid-19, sikap, perilaku penerapan 5M